Implementation of Children Rights Fulfilment In Bandar Lampung Special Development Institution For Childrens - Melista Aulia Nurdina (Constitutionale, 2021)
Protection of children faced in conflict with the law and undergoing a criminal period in the Special Development Institution for Children, their rights and needs must always be fulfilled. These children's rights consist of the right to education, skills guidance, health care, and others. This study aims to identify and analyze the fulfillment of children's rights that must be fulfilled in the Special Development Institution for Children. The problem in this research is children's rights that must be fulfilled in the Special Development Institution for Children. The method of implementing the fulfillment of children’s rights in the Special Development Institute for Children, factors that hinder the implementation of the fulfillment of rights in the Special Development Institution for Children. The approach to the problem used in this research is normative and empirical juridical. The data analysis in this study was conducted qualitatively. This study found that the rights of children in the Class II of Bandar Lampung Special Development Institution have been carried out well. The assisted children get formal and non-formal education; the assisted children receive self-development guidance such as hair shaving, electric welding, planting, and mind preservation. The assisted children are also free to play music, exercise, and perform worship according to their respective beliefs. Implementing the fulfillment of children's rights uses an individual approach, and its implementation uses an assessment. Officers have programs to fulfill children’s rights, such as service, guidance, implementation, and supervision. The author suggests that Class II of Bandar Lampung Special Development Institute’s officers can fulfill children's rights ranging from formal education, non-formal education, skills, self-development, religion, maximizing the individual approach method to assisted children so that they can know more about the backgrounds, needs, emotions and interests of these children, as well as improve the quality of existing advice and infrastructure.